FileMaker Pro design & scripting for dummies - Trimble, Timothy, 1957- (--For dummies., 2006)
Get the scoop on designing databases for Mac and Windows Use FileMaker Pro design and scripting to quickly, easily build databases that solve real problems FileMaker Pro has grown up, and it's better than ever! This easy-to-use guide shows you how to design a great FileMaker application, build a database that works, add the functionality you need, populate your database, and venture into programming with ScriptMaker. You'll find out how to share and protect your database, too. Discover how to Build a layout that works Create custom triggers and calculated fields Generate reports automatically Manage security Publish your database on the Web Embed pictures, sound, and video.